Electronic Government Implementation in the SIAPDES Application: A Study of the Department of Community and Village Empowerment, Central Kalimantan Province - Muhamad Alif Rofid; Nurul Hikmah; Intan Kumalasari (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
This study examines the implementation of Electronic Government through the SIAPDES Application at the Community and Village Empowerment Service of Central Kalimantan Province. SIAPDES is a web-based digital innovation designed to enhance efficiency, transparency, accountability, and village data management quality by integrating with population data. This research employed a qualitative case study approach at the Provincial PMD Office and two pilot villages (Telok Village and Maliku Baru Village). Data were gathered through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model. Findings reveal that the implementation of Electronic Government via SIAPDES has been initiated but is not yet optimal. Using the Harvard JFK School of Government framework (support, capacity, value), leadership support exists but lacks consistency in sustainability and budgeting. Capacity is constrained by infrastructure instability, operator turnover, server migration, limited human resources, and budget. Value is evident in archiving and monitoring but not maximized due to technical disruptions and lack of inter-agency integration. Supporting factors include leadership commitment and initial training, while inhibiting factors are uneven infrastructure, low digital literacy, and fragile program continuity. The study concludes that SIAPDES holds significant potential for village government digitalization but requires strengthened regulations, infrastructure, continuous training, and better system integration